Adipokines and Hepatic Insulin Resistance. (16th May 2013) - Li, Yu; Ding, Lin; Hassan, Waseem; Abdelkader, Daoud; Shang, Jing
Abstract : Obesity is a major risk factor for insulin resistance and type 2 diabetes. Adipose tissue is now considered to be an active endocrine organ that secretes various adipokines such as adiponectin, leptin, resistin, tumour necrosis factor-α, and interleukin-6. Recent studies have shown that these factors might provide a molecular link between increased adiposity and impaired insulin sensitivity. Since hepatic insulin resistance plays the key role in the whole body insulin resistance, clarification of the regulatory processes about hepatic insulin resistance by adipokines in rodents and human would seem essential in order to understand the mechanism of type 2 diabetes and for developing novel therapeutic strategies to treat it.